A critical review by using SWOT analysis to identifying risk in the Malaysian construction industry: case study evaluation - Abdulrahman, Al Tekreeti Ahmed Muneer; Haron, Nuzul Azam; Ales, Aidi Hizami; Hua, Law Teik (Genesis Global Publication, 2024)
Risk management is one of the most important project management tools that can predict unconfirmed events and risks during the project implementation period. To obtain a high level of performance to complete the project, most project managers are keen to implement and use this tool within the project life cycle effectively. To identify the potential impacts of risks, enhance positive certainty and reduce the effects of negative uncertainty, a series of risk management processes or activities are used that in turn identify, analyses and interact with project risks. When we compare the higher developed countries with other less developed countries, we find that the application of risk management is widespread and effective, in Malaysia, which is trying to be a developing country that can be affected by social, technological, economic, political and environmental risks, so the risk management in projects is not considered a fixed approach that can be adopted and that needs to be developed and continuous research. During the planning and implementation phases of the project, risk management can play an important role in making critical and accurate decisions that reflect positively on the project and make the status clearer through the preparation of an integrated approach to potential risks. Despite this, risk management systems and methods of treating them are sometimes well implemented in the construction industry, projects are affected by several factors such as stakeholders, agreements, laws and the project environment, which can generate potential risks and consider it a unique and important event that requires good and effective management and treatment. In this study, some previous and recent literature has been relied upon to obtain information related to risk management systems in the construction industry in Malaysia and the extent of their effectiveness and their impact on the project. This study was based on previous data that were re-analyses and the risks identified by using the SWOT tool. This was applied to data related to 4 construction projects in Malaysia, and the SWOT tool was developed to clarify the causes of problems, strengths, and weaknesses in those projects and give the necessary recommendations for that. The results reveal that there is still a big gap between the management of construction projects in Malaysia and the use of known methods of risk management, which means that there is a clear and large lack of risk management application systems in the construction industry, which requires comprehensive awareness of project departments like engineers and contractors and obligating them to implement the risk management system. also, it is possible to enact relevant laws to reduce the risk in projects, which will positively affect the Malaysian construction industry.